Common fears of patients undergoing bronchoscopy - Poi, P.J.; Chuah, S.Y.; Srinivas, P.; Liam, C.K. (European Respiratory Society, 1998)
In the world of medical literature, little has been reported about the fears of patients undergoing bronchoscopy. The aim of this study was to identify the common fears of patients undergoing fibreoptic bronchoscopy and to determine whether any factors might contribute to reducing these fears. One hundred and four consecutive patients undergoing bronchoscopy were interviewed. Sixty one patients expressed fear about the procedure, as follows: afraid of pain (33); afraid of breathing difficulties (11); afraid of oropharyngeal irritation (5); afraid of the bronchoscopy findings (2); afraid of sedation, cross-infection and nasal lignocaine spray, respectively (3); and unable to be specific (7). There was no difference between the "no fear" and "fearful" groups in ethnicity, source of referral, education, previous endoscopy, doctors' explanation and the patients' understanding of the procedure and its indication. "Fearful" patients were significantly younger (t=2.082, p=0.037) and female (chi2=4.180, p=0.038). Doctors were more likely to explain the indication for bronchoscopy than how it would be performed (chi2=6.403; p=0.011), and patients were more likely to understand why they needed a bronchoscopy than how it would be performed (chi2=21.505; p<0.001). Fear preceding bronchoscopy is independent of patients' demographic features except for age and gender. Doctors tend to explain "why" but not "how" the procedure is performed. Provision of detailed information about sensations that are likely to be experienced in bronchoscopy could be used to allay some of these common fears.